Persistent increase of β‐hCG level after salpingectomy in tubal pregnancy: Good or bad news? - Pinto Ribeiro, Pedro Cristiano (Clin Case Rep, 2021)
Heterotopic pregnancy is a rare event in natural conception (1:30000). We describe a case of a 36‐year‐old nulliparous. She presented to our department in the 4 + 6 gestational week with two simultaneous pregnancies intrauterine and extrauterine. Here, we compare treatment options and ultrasound findings to help examiners avoid inadequate therapeutic approaches.